Acute Effects of Photobiomodulation Therapy Combined with Static Magnetic Field in C2C12 Muscle Cells Exposed and Not Exposed to H2O2 - Marcos Vinicius Ferlito; João Vitor Ferlito; Fernando Joel Scariot; Mirian Salvador; Ernesto Cesar Pinto Leal-Junior; Thiago De Marchi; Catia Santos Branco (Applied Sciences)
Photobiomodulation (PBM) has been applied in biomedical technology to improve cellular responses. Specifically in sports medicine, it is used to accelerate metabolic and structural repair and adaptation in skeletal muscle under stress overload. Currently, PBM has been associated with static Magnetic Field (sMF) in clinical applications, enhancing the effects displayed by PBM when used in isolation. However, the biochemical and molecular effects of PBM-sMF in myoblasts remain unknown. This study aimed to investigate the effects of PBM combined with static magnetic field (PBM-sMF) at different doses in C2C12 muscle cells in the presence or absence of hydrogen peroxide (H2O2), a standard oxidant. Different spectrophotometric and fluorometric assays were conducted after cellular treatments. PBM-sMF was shown to be effective compared to H2O2 regarding cell viability and release of nitric oxide (NO), dsDNA, and reactive oxygen species (ROS) levels. It positively modulated mitochondrial membrane potential (ΔΨm) and cytochrome c oxidase (COX) activity under normal conditions and restored both to normal levels when impacted by H2O2. Regarding apoptosis, the recovery in viable cells observed on PBM-sMF treated cells was dose-dependent. In conclusion, PBM-sMF has a biphasic effect in normal and oxidative environments and may differently modulate myoblast cells depending on their redox status.